The role of movies in motivating students' speaking skills: An investigation toward English Education students - Sofiana, Nala Izza; Saraswati, Girindra Putri Dewi (ELT Forum: Journal of English Language Teaching, 2025)
This study explores the role of movies as a medium for learning English among English Education students. It highlights the significance of English as a global language and the challenges faced by learners, particularly in developing speaking skills. This study employed a qualitative approach to investigate students’ perceptions of how movies contribute to language acquisition, motivation, and cultural understanding. Data were collected through closed-ended questionnaires and semi-structured interviews, focusing on students’ experiences with English movies. Findings indicate that students prefer using movies over traditional methods as they provide an engaging context for learning vocabulary, pronunciation, and conversational skills. Additionally, movies foster intrinsic motivation by creating enjoyable learning experiences and reducing anxiety associated with speaking. The study highlights the potential of film to enhance language proficiency and motivate learners, suggesting that integrating movies into English language education can improve both linguistic and socio-cultural competencies.